Ekosistem Terumbu Karang Pulau Arborek Raja Ampat, Papua Barat - Dian Sutono HS; Robert Perangin-angin; Mustasim Mustasim (Jurnal Airaha, 2020)
Raja Ampat Regency is known to have tropical marine biodiversity which is estimated to be the richest in the world at the moment. Potential coral reef resources owned by Raja Ampat Regency, are part of the "Coral Triangle" (Coral Triangle) with the coral reef ecosystems in shallow exposure on almost all of the islands. Arborek Island is one of the Marine Protected Areas (MPA) destinations of tourists who enter the Meos Mansar Raja Ampat District, West Papua." Primary data collection was carried out by the line transect method (Line Intercept Transect) along the 50-meters transect at a depth of 8-10 meters, with data analysis covering the percentage of coral cover, the diversity index (H’), evenness index (E), and dominance index (C) ). Based on the results of data analysis, the condition of coral reefs in Arborek Island waters has coral cover values between 11.33% - 64.67%, diversity index between 1.20 - 2.87, evenness index between 0.13 - 0.41, and dominance index between 0.16 - 0.60.